(untitled) (Research, Society and Development, 2022)
Background: Asthma is a chronic inflammatory disease of the airways in which the inflammatory process culminates in recurrent episodes of wheezing, dyspnea, chest tightness and coughing. Recent studies have linked low serum levels of 25-hydroxyvitamin D (vitamin D) to severe asthma exacerbations, decreased lung function, and reduced response to corticosteroids. Objectives: To analyze the effects of the use of vitamin D in patients with asthma, with or without defect in this vitamin. Methods: This is an integrative review, which used PUBMED, SciELO and LILACS databases. Inclusion criteria were: answering the guiding question, being available in Portuguese, English or Spanish, articles published in the last 5 years, of the clinical trial type, reports and case series, cohort studies and cross-sectional studies. After screening, 13 articles were selected. Results and discussion: The results were quite divergent regarding the effectiveness of vitamin D supplementation in asthmatic patients with or without its deficiency, although the majority indicated a strong correlation between vitamin D deficiency and the exacerbation of asthma attacks. Still, factors such as sample type and size and follow-up time can influence the results, showing that there is a more positive correlation in children than in adults. Conclusion: The divergent results in the available literature require that more primary studies be carried out, with a larger and more homogeneous sample, in order to reach more reliable results, which, in fact, support the effectiveness of vitamin D supplementation in these patients.